Μελέτη Τάξης Προσανατολισμού στον Υγρό Κρύσταλλο 4-n-pentyloxyphenyl 4-n-octyloxybenzoate και το Υβριδικό του Σύστημα με Κβαντικές Τελείες CdSe-ZnS Μέσω Φασματοσκοπίας Raman Πολωμένου Φωτόςκαι Δεδομένων Διπλοθλαστικότητας - Κύρου, Χριστίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2015)
Orientational order is one of the most significant properties that characterizes the liquid crystalline phases and correlates with the anisotropic behaviour of these substances.We report measurements of the temperature dependence of the vibrational Raman depolarization ratios and optical birefrigence in the Isotropic and Nematic phase of the pure nematic liquid crystal 4-n-pentyloxyphenyl 4-n-octyloxybenzoate made of rod-like molecules , in order to evaluate the order parameters as a function of temperature.The analysis of our data , in combination with bibliographic methods , also enabled us to determine the molecular polarizability and the anisotropy of polarizability of the liquid crystalline substance. The measurements have been performed by polarized micro-Raman and polarized light microscopy techniques. The obtained results for the order parameters were compared with those of a mixture of the liquid crystalline compound with semiconducting quantum-dots nanoparticles CdSe-ZnS of 1,44% concentration in weight , that were treated to be hydrophobic , in order to determine the impact of the nanoparticles on the orientational order and the microstructure of ttha sample.